In the Meantime: Duncan Campbell Scott's In the Village of Viger - Lynch, Gerald (Studies in Canadian Literature, 1992)
W.H. New claims that Duncan Campbell Scott's In the Village of Viger is the first in a rich tradition of Canadian short story cycles. It is also an expression in fiction of turn-of-the-century North American anti-modernism. The primary thematic concern of the collection is the threat posed by the advance of metropolitan modernity upon the traditional conception of the family and the ideal of community itself. The culminating story, "Paul Farlotte," explores the dominant theme of the fractured family, in concert with other themes from the preceding stories: madness, romance, industrialization, and "progress". In the stories, Scott envisions the possibility of a new order emerging, in which the concepts of "family" and "community" would be redefined without losing their traditional functions of conserving and transmitting values.